2006
DOI: 10.1007/s00125-006-0336-y
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ agonism increases rat adipose tissue lipolysis, expression of glyceride lipases, and the response of lipolysis to hormonal control

Abstract: Aims/hypothesis The aim of this study was to investigate the effect and mechanisms of action of in vivo peroxisome proliferator-activated receptor γ (PPARγ) activation on white adipose tissue (WAT) lipolysis and NEFA metabolism. Materials and methods Study rats were treated for 7 days with 15 mg/kg of rosiglitazone per day; control rats were not treated. After a 6-h fast, lipolysis and levels of mRNA for lipases were assessed in explants from various adipose depots. Results Rosiglitazone markedly increased bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
93
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 40 publications
23
93
0
Order By: Relevance
“…Secondly, whereas HSL expression remained unaffected, both treatment conditions exerted a stimulatory effect on mRNA levels of the lipolytic enzyme ATGL, which in this case was additive. This confirms our previous finding that ATGL is a target of PPARg agonism, 43 and reveals the as yet unrecognized positive modulation of ATGL expression in vivo by CORT. The GC-mediated induction of adipose tissue lipolysis was until now thought to be due to facilitation of catecholamine action 45 and interference with that of insulin.…”
Section: Pparc In Rats With Hypercorticosteronemia M Berthiaume Et Alsupporting
confidence: 91%
See 1 more Smart Citation
“…Secondly, whereas HSL expression remained unaffected, both treatment conditions exerted a stimulatory effect on mRNA levels of the lipolytic enzyme ATGL, which in this case was additive. This confirms our previous finding that ATGL is a target of PPARg agonism, 43 and reveals the as yet unrecognized positive modulation of ATGL expression in vivo by CORT. The GC-mediated induction of adipose tissue lipolysis was until now thought to be due to facilitation of catecholamine action 45 and interference with that of insulin.…”
Section: Pparc In Rats With Hypercorticosteronemia M Berthiaume Et Alsupporting
confidence: 91%
“…29,35,36 Knowledge of the detailed mechanisms by which GC impact adipose tissue lipid metabolism remains fragmentary; however, a permissive action on the insulin-mediated stimulation of LPL, 37,38 an inhibitory effect on the anti-lipolytic action of insulin, 39 direct transcriptional activation of the fatty acid-synthesizing gene FAS, 40 and inhibition of the expression of the fatty acid re-esterification gene PEPCK 41 have been established. In the case of PPARg, effects on adipose tissue lipid metabolism are manifold and include stimulation of lipid uptake, esterification, recycling, lipolysis, and oxidation, 11,[42][43][44] with an overall preponderance of lipid retention over fatty acid release pathways explaining fat accretion. 11 Therefore, the GC and PPARg pathways are liable to interact either positively or negatively at several levels of adipose tissue metabolism.…”
Section: Pparc In Rats With Hypercorticosteronemia M Berthiaume Et Almentioning
confidence: 99%
“…These findings are consistent with reports of other investigators showing that long-term treatment with different TZDs including rosiglitazone can also promote increases in lipolysis under some circumstances. [10][11][12] In addition, we found that chronic pioglitazone treatment was associated with reduced NEFA reesterification. Despite these effects on NEFA metabolism in adipose tissue, long-term treatment with pioglitazone induced decreases in circulating levels of NEFA.…”
Section: Discussionmentioning
confidence: 65%
“…For example, some studies have shown that administration of TZDs, troglitazone, darglitazone or rosiglitazone, for 4 weeks can increase the capacity of adipose tissue to release NEFA. 10,11 In addition, Festuccia et al 12 reported that rosiglitazone treatment for 1 week was associated with increased basal and noradrenaline-stimulated NEFA and glycerol release from adipose tissue. Therefore, in this study in a rat model of the metabolic syndrome, we investigated the effects of long-term administration of pioglitazone (4 months) on adipose tissue lipolysis and NEFA metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, FATP mRNA expression is up-regulated by a PPARγ agonist (10). Moreover, a PPARγ agonist stimulates lipolysis to release fatty acids from the membrane (11). It is possible, therefore, that the decreased uptake of arachidonic acid on the treatment of HCA-7 cells with indomethacin involves the activation of PPARγ followed by the export and / or lipolysis of the initially incorporated labeled arachidonic acid.…”
mentioning
confidence: 99%